Fostering democracy and stability in Timor-Leste after the 2006 crisis: on the benefits of coordinated and cooperative forms of support - Karina Mross (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Aiming to gain deeper knowledge of the impact that external engagement can have in fragile contexts, this paper analyses international support given to foster stability and democracy in Timor-Leste. Two main questions guided the research. First, have international actors contributed to the consolidation of peace and democracy in Timor-Leste? Second, which factors explain successful support, and which ones explain failure? After having achieved independence, the young nation faced a new task: establishing a stable state and a functioning democratic system. Four years after formal independence had been established, a major violent crisis forced the government to invite an international stabilisation force. The crisis revealed not only that stability was still fragile, it also disclosed the many persistent challenges. Since then, considerable achievements have been made: solving the crisis of massive internal displacement caused by the 2006 events, and conducting two elections without major incidents, in 2007 and in 2012. However, problems in the security sector, which were closely linked to the outbreak of the 2006 crisis, still have not been comprehensively addressed. The international community provided substantial support to all of these processes, helping to facilitate important accomplishments, yet failing to prevent – or even reinforcing – some weaknesses as well. The research uses selected “critical junctures” in the peace and democratisation process to assess the impact of donor engagement. The analysis focuses on these critical junctures in order to establish what impact they had and to infer the causality of donors' support. International engagement claiming to have made a crucial contribution to the overall process should be visible in these critical junctures, while significant contributions to such critical junctures will, by definition, also have had an impact on the larger peace and democratisation processes. The critical junctures analysed are: 1) the 2007 electoral process, 2) the crisis of internal displacement (2006-2010) and 3) Security Sector Reform (2006-2014). In order to analyse which factors influenced the effectiveness of external support, the research was guided by academic literature, which suggests that both choosing cooperative over coercive forms of cooperation as well as high levels of coordination increase the effectiveness of international support given to advance peace and democracy. Both of these expectations were generally confirmed by this research: high levels of coordination indeed helped to render external support effective, whereas low levels significantly hampered its success, as diverging approaches in the security sector show, in particular. Cooperative forms of support have been more successful, as illustrated by the very successful international facilitation of the government-led resolution of the internal displacement crisis. More coercive measures in the Security Sector Reform process provoked resistance and reduced the effectiveness of international support. Yet, the analysis also shows the limits of cooperative forms of support when framework conditions are unfavourable.
Keywords: 320